Identification of Urinary Biomarkers for Exercise-Induced Immunosuppression by iTRAQ Proteomics. (25th January 2020) - Xu, Guoqin; Lin, Wentao; McAinch, Andrew J; Yan, Xu; Weng, Xiquan
Abstract : Purpose . To identify noninvasive immune biomarkers of exercise-induced immunosuppression using the iTRAQ proteomics technique. Methods . Fifteen healthy males were recruited and subjected to a four-week incremental treadmill running training program. After each week of training, WBC counts and CD4 + and CD8 + lymphocytes were measured to monitor the immune function status. iTRAQ proteomics technology was used to identify differential proteins and their characteristics in urine. Results . Our data showed that the WBC counts, CD4 + lymphocytes, and CD4 + /CD8 + ratio decreased by more than 10% after four weeks of training, suggesting exercise-induced immunosuppression. A total of 1854 proteins were identified in urine during the incremental running using the iTRAQ technology. Compared with the urine before training, there were 89, 52, 77, and 148 proteins significantly upregulated and 66, 27, 68, and 114 proteins significantly downregulated after each week, respectively. Among them, four upregulated proteins, SEMG-1, PIP, PDGFRL, and NDPK, increased their abundance with the increased exercise intensity. Bioinformatics analysis indicates that these proteins are involved in stress response and immune function. Conclusion . Four weeks of incremental treadmill running induced immunosuppression in healthy males. By using iTRAQ proteomics, four proteins in the urine, SEMG-1, PIP, PDGFRL, and NDPK, were found to increase incrementally with the increased exercise intensity, which have the potential to be used as noninvasive immune biomarkers of exercise-induced immunosuppression.